The transforum model transforming agro innovation toward sustainable development - van Latesteijn, Henk; Andeweg, Karin (Springer Netherlands, 2011)
The TransForum Model: Transforming Agro-innovation Toward Sustainable Development presents new insights on how to use innovation for the complex challenge of sustainable development. Innovation has been at the heart of the positive agricultural developments in both production and productivity growth during the last decades. Due to the negative impact of these developments on the physical and social environment, a transformational change of the agricultural sector is needed to shift toward a more sustainable development. Changing the agro innovation system is necessary to bring this about. In this book, six years of experimenting with sustainable development in agriculture is translated into a set of principles and guidelines. Together these constitute The TransForum Model to deal with innovation and sustainable development. This book shows how different scientific disciplines contribute to this new mode of agro innovation.